IMPLEMENTASI CONTIONOUS INTEGRATION DAN CONTINOUS DEPLOYMENT PADA APLIKASI LEARNING MANAGEMENT SYSTEM DI PT. MILLENNIA SOLUSI INFORMATIKA - Ari Purno Wahyu; Indra Guna Noviantama (Universitas Widyatama, 2021)
Learning Management System or LMS is an application product developed by PT. Millennia Solusi Informatika. This LMS aplication has been used by a private school network. The application is developed using scrum method where this method approach is agile and can adjust requirements quickly. Based on this, in process of delivering the software, it is necessary to use the concepts of continuous integration and continuous deployment in order to fulfill an agile and iterative development flow. Continuous integration (CI) is the integration of code into repository code then run deployment, quickly and more frequent. While Continuous Deployment or Continuous Delivery (CD) is a practice that carried out after CI process is complete and all code is successfully integrated, so that application can be build and release automatically. By Using CI/CD, the application delivery process can continue automatically, quickly and often even though the application has been used by the user